Infringement of General Election Ethics in Riau Islands Province, Indonesia - Barta Oktarius Barus; Arry Bainus; Muradi Muradi (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2020)
Violation of ethics that involves the General Election Committee members is due to less concern to the process of the development of democracy. Several cases show that the organizers of the election went to the ethics trial of the Honorary Council of Election Management Bodies (Dewan Kehormatan Penyelenggara Pemilu, DKPP). This research analyzes the factors that cause the violation of ethics in the General Election in the Riau Islands province. This study applies qualitative methods and managed some interviews, field visits, and library research to collect data. This study employs the theory of institutional capacity from Christensen and Gazley (2008) to analyze the collected data. The theory views the institution from four dimensions to identify the problems in the violation of ethics, namely, human resources, external factor, infrastructure, and financial. Human resources as the organizers of the general election know less the regulation and manuals that regulate the election, which results in the violation of ethics. This study seeks to know the factors that cause the violation so it can contribute to the general election’s organizers to improve their knowledge and organize the election with integrity.